(untitled) (Годишен зборник на Филозофски факултет - Скопје, 2021)
As a result of the increased prevalence of dual careers, digitalization, and changes in the work arrangements, research on the work-life interface and its management come to be very important. The aim of this study was to explore psychometric properties of the Measure of boundary flexibility for work and family domains in Macedonian context using a sample of 200 teachers in primary, secondary, and higher education. Exploratory factor analysis (EFA, principal axis factoring with promax rotation) was performed to assess the factorial validity of the scale. For further investigation of its construct validity correlation among extracted four factors (dimensions of boundary flexibility) and set of other relevant work-life constructs were analyzed. Scale reliability was estimated using internal consistency coefficients. In line with the factor model of the original scale, EFA results in this study revealed four factorial structures, i.e. work flexibility ability, work flexibility willingness, family flexibility ability, and family flexibility willingness factors were identified. An exception was one item that loaded on the work flexibility ability factor, while originally was part of the work flexibility willingness factor. All factors/ subscales showed satisfactory internal consistency. Findings, in general, indicated adequate psychometric characteristics of the measure, suggesting that the Measure of boundary flexibility could be used for research purposes in the Macedonian context. However, future study applying multi-group confirmatory factor analysis in order to provide evidence for the model invariance is needed.